Implementasi Strategi Keuangan Dalam Novel “Home Sweet Loan” Karya Almira Bastari - Andre Wahyu Kusuma,; Azis Nurdiansyah ,; Eva Dwi Kurniawan, (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research aims to analyze the financial strategies of four characters in the novel "Home Sweet Loan" by Almira Bastari, focusing on how they manage their finances to purchase a house or assets, considering their different economic backgrounds. The research method employed is hermeneutic, utilizing a qualitative approach. The primary source of data is derived from the novel "Home Sweet Loan," published by Gramedia Pustaka Utama in 2022 (Fourth Edition: September 2023). The research findings reveal various financial strategies, including financial management, insurance, leasing, asset management, and savings, implemented by the characters in different economic contexts. This study provides insights into the approaches that individuals with diverse economic backgrounds can take in planning their finances for the future.